Bimbingan Teknis Literasi Numerasi Pada Kurikulum Prototype Pendidikan Dasar Di Kabupaten Malang - Nulinnaja, Ratna; Faridah, Siti; Putra, Kivah Aha (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Increasing the quality of teachers in preparing literacy and numeracy questions through technical guidance activities on numeracy literacy so that they are able to support the implementation of the curriculum according to the standards set by the government. Changes in the curriculum in Indonesia encourage teachers to always be able to develop their abilities in terms of preparing valid questions so that it has an impact on the appropriateness of the assessments prepared by teachers. The government's socialization is still uneven due to the pandemic, so the team has mobilized to serve UIN Maulana Malik Ibrahim Malang to participate in socializing the material at MIS Almaarif 09 Randuagung Singosari and MI Ar Raudhah Lawang. The method used is Participatory Action Research (PAR). The theory used in this service, namely Maslow's theory, results in an increase in teacher quality, especially the ability to understand numeracy literacy material and develop valid numeracy literacy questions. Technical guidance activities are carried out in 4 stages, namely observation, providing material, then practical activities and evaluation. The resulting teacher response was 31.3%, the result was strongly agree, which showed a positive response, then 62% of them responded in agreement, so the percentage certainly shows the success of the implementation of technical guidance which can be seen from the way the teacher prepares numeracy literacy questions in accordance with the characteristics standardized by the government in the new curriculum.